Determining the frequency and severity of malnutrition and correlating it with the severity of liver cirrhosis - Iftikhar Haider NAQVI,; Khalid MAHMOOD,; Sirajus SALEKEEN,; Syed Tehseen AKHTER, (Turkish Journal of Gastroenterology, 2019)
-